“THE EU CONSTITUTION IS DEAD — LONG LIVE THE REFORM TREATY” — BUT WILL IT MAKE THE EU MORE DEMOCRATIC, EFFICIENT AND TRANSPARENT? - Hofmeister, Hannes (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2008)
This article deals with a highly topical issue in European Law and Politics: the European Union Reform Treaty. It outlines the key changes introduced by the Treaty, then subjects them to a critical analysis. In particular, it examines whether the amendments made will render the European Union more democratic, more efficient and more transparent. The specific issues addressed include the new voting procedure in the Council, the enhanced role of national parliaments and the European Parliament, the new post of President of the European Council, the legal personality of the Union as well as the new citizens’ initiative.